Rescue on the Oregon trail - Messner, Kate.; McMorris, Kelley (New York : Scholastic Press, 2015)
Ranger, a golden retriever, could have been a great search-and-rescue dog except for the squirrels, but one day he unearths a mysterious box and finds himself transported back to the year 1850, where his faithful service is really needed by a family traveling west along the Oregon Trail.
Includes bibliographical references.
Publisher's Weekly, November 2014.
Kirkus Review, November 2014.
4.5.
3-6.
690L
Keywords: Golden retriever -- Juvenile fiction; Time travel -- Juvenile fiction; Golden retriever -- Fiction; Dogs -- Fiction; Time travel -- Fiction; Adventure and adventurers -- Fiction; Time travel -- Fiction; Golden retriever -- Fiction; Working dogs -- Fiction; Time travel -- Fiction; Oregon National Historic Trail -- Juvenile fiction; West (U.S.) -- History -- 1848-1860 -- Juvenile fiction; Oregon National Historic Trail -- Fiction; Oregon Trail -- Fiction; West (U.S.) -- History -- 1848-1860 -- Fiction; Adventure fiction